(untitled) (Revista Sistemas de Producción Agroecológicos, 2017)
In order to evaluate the effect of the inclusion of scales and fish bones as sources of calcium and phosphorus, on the zootechnical performance of Japanese quail stance phase. 200 birds of 70 days of age were used for 26 weeks, which were distributed in a completely randomized experimental design with four treatments, five replicates and 10 birds each. The treatments consisted of including fish scales and bones at the following levels: 0; 0.54; 1.08 y 1.62%. Egg production was: 84.3, 85.6, 86.1 and 79.5%; daily consumption: 25.4, 25.6, 25.2 and 24.3 g; feed conversion: 0.398, 0.401, 0.409 and 0.392 kg of ration/dozen eggs; egg mass: 2.90. 2.84, 2.66 and 2.89; for levels with 0. 0.54, 1.08 and 1.62%, respectively. The results indicate quadratic increase (P<0.05), according to equation: Y = -7.9401x2 + 9.4237x + 83.96, R² = 0.897, by effect of fish scale and bones on the production and improvement of egg mass per kg of ration. In conclusion, these two sources of calcium and phosphorus can be included in the diet for quail in the posture phase up to 0.59% because they improve egg production and the feed conversion given in kg of ration/kg of egg, without affecting the other performance variables.